1984
DOI: 10.1111/j.1365-2125.1984.tb02544.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omeprazole on gastric emptying in patients with duodenal ulcer disease.

Abstract: The effect of a single oral dose of omeprazole (90 mg) on gastric emptying was assessed with a dual isotope scintigraphic technique in eight patients with a history of duodenal ulcer disease. Omeprazole had no significant effect on solid or liquid gastric emptying. The bioavailability (AUC0‐2 h) of omeprazole in all patients was greater than that required for total suppression of acid secretion. No adverse clinical or laboratory effects were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 13 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Thus, studies about the potential impact of PPIs on gastric emptying have clinical relevance. To date, the variable effects of omeprazole [5, 6] and lansoprazole [7, 8] on gastric motor function have been reported. It is considered that PPI-induced acid suppression with or without hypergastrinemia indirectly affects gastric motility [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies about the potential impact of PPIs on gastric emptying have clinical relevance. To date, the variable effects of omeprazole [5, 6] and lansoprazole [7, 8] on gastric motor function have been reported. It is considered that PPI-induced acid suppression with or without hypergastrinemia indirectly affects gastric motility [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…22 Yet, these studies are far from explaining the effects of PPIs on pylorus activities. Relexant or inhibitory effects of PPIs at high doses were demonstrated on vascular precontracted smooth muscle, gallbladder, prostate, corpus cavernosum, myometrium, and lower esophageal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the stomach was alkalinized by intragastric infusion of 7%sodium bicarbonate, an increase of gastric motor activity was found in only 2/7 subjects. In addition, since it has been reported that upper gastrointestinal motility is not increased by omeprazole, a proton-pump inhibitor which more potently inhibits gastric acid secretion than H2-receptor antagonists (28,29), the rise in intragastric pH does not appear to be the only cause of the increase in gastrointestinal motility.…”
Section: Les Pressure Associated With Gastric Phasic Motor Activity Imentioning
confidence: 99%